Crystal structure of [(4-bromobenzyl)triphenylphosphonium] tetrabromoantimony(III), [C25H21BrP]+[SbBr4]− - Li Xue; Wang Guangyao (Zeitschrift für Kristallographie - New Crystal Structures)
C25H21Br5PSb, monoclinic, P21/c (no. 14), a = 10.5893(1) Å, b = 14.7743(2) Å, c = 18.9737(3) Å, β = 102.279(1)°, V = 2900.52(7) Å3, Z = 4, Rgt(F) = 0.0481, wRref(F2) = 0.1362, T = 293(2) K.